2016
DOI: 10.3390/cancers8100097
|View full text |Cite
|
Sign up to set email alerts
|

The Role of TAM Family Receptors in Immune Cell Function: Implications for Cancer Therapy

Abstract: The TAM receptor protein tyrosine kinases—Tyro3, Axl, and Mer—are essential regulators of immune homeostasis. Guided by their cognate ligands Growth arrest-specific gene 6 (Gas6) and Protein S (Pros1), these receptors ensure the resolution of inflammation by dampening the activation of innate cells as well as by restoring tissue function through promotion of tissue repair and clearance of apoptotic cells. Their central role as negative immune regulators is highlighted by the fact that deregulation of TAM signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
101
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 158 publications
(310 reference statements)
2
101
0
Order By: Relevance
“…Cabozantinib is an inhibitor of multiple receptor tyrosine kinases including VEGFR, MET, the TAM kinases, KIT, FLT3, TRKB, and TIE2 (43). In addition to their roles in angiogenesis, tumor growth, and metastasis, several targets of cabozantinib play a role in immunosuppression, particularly VEGFR, MET, and the TAM kinases (17,(44)(45)(46). Inhibition of these signaling molecules likely contributes to the antitumor immunomodulatory effect of cabozantinib ( Fig.…”
Section: Combining Checkpoint Inhibitors With Cabozantinib: Preclinicmentioning
confidence: 99%
See 1 more Smart Citation
“…Cabozantinib is an inhibitor of multiple receptor tyrosine kinases including VEGFR, MET, the TAM kinases, KIT, FLT3, TRKB, and TIE2 (43). In addition to their roles in angiogenesis, tumor growth, and metastasis, several targets of cabozantinib play a role in immunosuppression, particularly VEGFR, MET, and the TAM kinases (17,(44)(45)(46). Inhibition of these signaling molecules likely contributes to the antitumor immunomodulatory effect of cabozantinib ( Fig.…”
Section: Combining Checkpoint Inhibitors With Cabozantinib: Preclinicmentioning
confidence: 99%
“…This neutrophilmediated suppression was blocked by MET inhibition with a concomitant increase in tumor response to checkpoint inhibition (54). The TAM kinases play an important role in maintaining immune homeostasis and are expressed on innate immune cells such as DCs, macrophages, monocytes, and natural killer cells (45,46). TAM receptor triple-knockout mice develop multiorgan autoimmune disease, reflecting the normal physiologic role of these kinases in limiting immune responses.…”
Section: Combining Checkpoint Inhibitors With Cabozantinib: Preclinicmentioning
confidence: 99%
“…The TAM (Tyro3, Axl, MerTK) subfamily of transmembrane receptor tyrosine kinases (RTKs) has been shown to regulate normal physiological processes such as tissue homeostasis and innate immunity [1]. Consequently, dysregulation of TAM signalling has been associated with chronic inflammatory and autoimmune conditions [2][3][4]. In addition, TAM signalling has been implicated in cancers, where each TAM RTK has in different studies been shown to regulate cancer cell growth, survival, proliferation, differentiation, migration or invasion [1,5].…”
Section: Introductionmentioning
confidence: 99%
“…TAM ( T yro-3, A xl, and M er) receptor tyrosine kinases are essential regulators of immune homeostasis that dampen the activation of immune cells and restore tissue function by promoting tissue repair and clearance of apoptotic cells [68]. TAM-dependent pathways act as a negative feedback mechanism that suppresses inflammation [7].…”
Section: Introductionmentioning
confidence: 99%